PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTU MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA - Dwi Hilana Yesika; Meirza Nanda Faradita; Iswahyuni (PROCEEDING UMSURABAYA, 2024)
The use of learning media is a necessity for teachers in running the wheels of learning. The presence of learning media is very important because it can help teachers describe learning concepts in a real and fun way in the classroom. This study uses a qualitative descriptive research method with a location at Al Izzah Nature Elementary School, Krian District, Sidoarjo Regency. The research subjects were grade V students, totaling 28 students. The results showed that the use of discovery learning models assisted by audio-visual media in Indonesian language learning can improve significant results. This is indicated by the acquisition of post test data in cycle I and cycle II, the percentage of students who achieved success in cycle I increased from 46. 43% to 82. 14% in cycle II, according to the data on the assessment of learning outcomes in cycle II this increased to 35. 71%. And the acquisition of skill observation data also increased from 71. 43% to 89. 28%. The findings of cycle II allow it to be concluded that the discovery learning model supported by audio-visual media is an effective way of learning and has the potential to help students in improving Indonesian learning outcomes.